IDENTIFIKASI KETERAMPILAN PUSTAKAWAN DALAM MEMASARKAN DIGITAL REPOSITORY DI PERPUSTAKAAN STIKES YARSI PONTIANAK - Tania, Hanni; Nur Latifa Hanum, Atiqa; Sahidi, Sahidi (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2024)
Digital repository is a storage medium for the academic community that is open access. The selection of marketing media and content that has not attracted users utilizes digital repositories and affects the user level. The method used is qualitative with non-participant observation techniques, in depth interviews. Data analysis techniques through data reduction, data presentation, and conclusion, while data validity tests use credibility, transferability, dependability, and confirmability. The results showed that the skills possessed by librarians include 8 skills, namely: Digital marketing skills, direct marketing, policy aspect abilities, technical abilities, target analysis, information technology, marketing media creativity, managing time, evaluating. identification is carried out through the concept of 4P, marketing is not optimal for libraries and librarians externally.